The Value of Responsibility in the Storybook “Gambar Lucu Mika” by Tyas Widjati and Faza - Nurrochmah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Early childhood education is a crucial phase in shaping character and developing children's potential holistically, including the value of responsibility. The book Mika's Funny Drawings by Tyas Widjati and Faza serves as a relevant character education medium for young children, emphasizing the importance of responsibility through the main character, Mika. This study aims to analyze the values of responsibility within the book and its relevance to character education theories and moral development in children. Based on Erik Erikson’s psychosocial development theory and Piaget and Kohlberg’s moral development theory, Mika’s story portrays a child who dares to make choices, acknowledges mistakes, self-corrects, and considers the impact of his actions on others. This analysis shows that Mika's Funny Drawings is not only engaging as a reading material but also instrumental in shaping character, particularly the value of responsibility, for early childhood. The use of this story medium is expected to be an effective means of character education both in schools and at home, providing a foundational sense of responsibility that benefits children’s future development.